Non-violent resistance movements and substantive democracy. Issue 3 (3rd April 2023) - Fetrati, Jalal
ABSTRACT : Is the depth of democracy in newly established democratic regimes influenced by their mode of transition? Previous research has focused on violent and nonviolent resistance campaigns' effects on the durability and formal dimensions of democracy. In this article, I examine whether democracies resulting from nonviolent resistance movements are more successful in deepening democracy than those emerging from violent conflicts or elite-led top-down liberalizations. Combining difference-in-differences (DiD) estimation and kernel matching, I analyse all democratic transitions that occurred between 1900 and 2020, using V-Dem High-Level Democracy Indices for measuring formal and substantive dimensions of democracy, including (1) electoral democracy, (2) liberal democracy, (3) participatory democracy, (4) deliberative democracy, and (5) egalitarian democracy. I find a significant difference in the depth of democracy between democratic regimes forged from nonviolent resistance (NVR) campaigns and those born from violent revolutions and elite-led top-down liberalizations. This effect is statistically significant for up to ten years following the transition. I argue that the engagement and improvement of civil society before and during the transition is a key factor that explains why NVR-induced democracies are more successful in deepening the ideals of democracy and less susceptible to democratic backsliding.